The Cadzow Lake site (MjVi-1) a multi-component historic Kutchin Camp - Morlan, Richard E. (Mercury series., 1972)
Three occupations were identified (1850, 1880 and 1933) representing historic encampments of the Vunta Kutchin Athapascan speakers who still occupy the area to-day.